The spatial analysis for Bassia eriophora (Schrad.) asch. plant distributed in all Iraq by using RS and GIS techniques - al-Rimmahi, Fuad Kazim Mashi; al-Bahadili, Zaynah Khalil Ibrahim (Baghdad Science Journal., 2020)
Most vegetation’s are Land cover (LC) for the globe, and there is an increased attention to plants since they represent an element of balance to natural ecology and maintain the natural balance of rapid changes due to systematic and random human uses, including the subject of the current study (Bassia eriophora ) Which represent an essential part of the United Nations system for land cover classification (LCCS), developed by the World Food Organization (FAO) and the world Organization for environmental program (UNEP), to observe basic environmental elements with modern techniques. Although this plant is distributed all over Iraq, we found that this plant exists primarily in the middle and southern parts of Iraq in wet areas and near rivers or catchment area or water basins. The main idea is how to use this techniques to monitor the distribution of the plants (Bassia eriophora), in order to utilize and take provisions of plant growth and diffusion, Moreover, know and control the breadth of these areas in Iraq and prepare for them, and understanding climates and the variable plantation habitats and mapping patterns, may lead to a successful environmental protection and dominance plan. In this study, monitoring the distribution of Bassia eriophora in Iraq by apply remote sensing (RS) and geographic information systems (GIS) techniques. The data was obtained from (BAG) National Herbarium of Iraq, Ministry of Agriculture. (BUNH) Iraq Natural History Research Centre and Museum, University of Baghdad the University Herbarium (BUH) in College of Science at University of Baghdad. This data contains only the address (place of germination), this information (addresses) was detected, identified and covered for all areas sampled by the techniques of satellite imagery and images taken from the air and some data records where the main features of these areas.